(3eYGQL GdUYhO Edi fjd Mce LdH GdShOs - (3GdJfHcJj , CMeO HGHG Hf CMeO Hf CMeO Hf YeQ GdJcQhQj GdShOGfj, CHh GdYHGS,J (B1036 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bOe Edi SDGd efP KdGK Sfjf hCRjO ef HdGO fhGJ s
(3BNQgG (B:s
(3hdjcf gPG BNQ eG JjSQ ef eYGQL GdUYhO Edi fjd Mce HLdH GdShO hEf TFJ aSeg GdcTa hGdHjGf dCUfGa eLdhH GdShOGf s
(3HgG fXGe GdJYbjHIs
(3aQZ efg GdeDda SfI (B1024s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B102 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B145s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3Gdabg GdeGdcjs